IMPLEMENTATION OF REHABILITATION OF VICTIMS OF DRUG ABUSE ACCORDING TO LAW NUMBER 35 OF 2009 IN THE REVIEW OF MAQASID SYARIAH STUDY AT BAITU SYIFA REHABILITATION CENTER MEDAN): IMPLEMENTASI REHABILITASI KORBAN PENYALAHGUNAAN NARKOBA MENURUT UNDANG-UNDANG NOMOR 35 TAHUN 2009 DALAM TINJAUAN MAQASID SYARIAH (STUDI DI PANTI REHABILITASI BAITU SYIFA MEDAN) - Nanang Ardiansyah Lubis; Zulkarnain Zulkarnain; Ramadhan Syahmedi Siregar (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
This study aims to analyze the implementation of rehabilitation for drug abuse victims based on Law No. 35 of 2009 on Narcotics and the application of Sharia principles in the rehabilitation practices at Baitu Syifa Drug Rehabilitation Center, Medan. Drug abuse in Indonesia has become a critical issue with multi dimensional impacts on health, society, economy, and law. Hence, integrating positive legal measures with Islamic values offer sastrategic alternative for addressing drug-related problems humanely and effectively. Using a juridical-empirical approach and a descriptive qualitative method, this research collected data through in-depth interviews, field observation, and document analysis. The findings reveal that the rehabilitation program at Baitu Syifa complies with Articles 54 and 103 of Law No. 35/2009, emphasizing medical and social recovery for addicts and victims. Furthermore, the center incorporates Sharia principles, particularly hifzhal-nafs (protection oflife) and hifzhal-‘aql (protection of intellect), through spiritual activities such as congregational prayers, religious studies, remembrance (dhikr), and moral counseling. These efforts enhance the physical, psychological, and spiritual well-being of residents, supporting their reintegration into society. Nevertheless, the study identifies several challenges, including inadequate facilities, lack of specialized personnel, and social stigma against former addicts. Therefore, strong collaboration between government, religious institutions, and the community is essential to create a holistic and sustainable rehabilitation system. This research contributes to the academic discourse on law and Islamic studies by emphasizing the integration of legal and spiritual dimensions in promoting human welfare, moral integrity, and national resilience.